It looks like you're given
![f(x) = 1012x^(101) - 72x^(75) + \pi x^2 - e^(2x) + 100346](https://img.qammunity.org/2023/formulas/mathematics/college/yqniobknc6lziu4c7iqmvr607zfmtjros5.png)
and are asked to find the 102nd derivative of f(x).
Recall the power rule: for integer n,
![\displaystyle \left(x^n\right)' = nx^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/ss0pldxjt3e2aajvenxj4izpxh3rpw7c7g.png)
This means that the power of x reduces to 0 after differentiating n times, and you're left with a constant coefficient n! :
• after differentiating 2 times,
![\left(x^n\right)'' = \left(nx^(n-1)\right)' = n(n-1)x^(n-2)](https://img.qammunity.org/2023/formulas/mathematics/college/fzldq4b7nhhlo7k0x2bc2yq798cee6hlhx.png)
• after differentiating 3 times,
![\left(x^n\right)^((3)) = \left(n(n-1)x^(n-2)\right)' = n(n-1)(n-2)x^(n-3)](https://img.qammunity.org/2023/formulas/mathematics/college/ky65ojc3qnf51q5za74v7v5ctehv385nt3.png)
• and so on, up to the n-th time, which yields
![\left(x^n\right)^((n)) = n(n-1)(n-2)\cdots*2*1x^(n-n) = n!](https://img.qammunity.org/2023/formulas/mathematics/college/qzisicuzd3598doz4kq8hd502au6li10c3.png)
As soon as you have a constant, the next derivative will be 0. This means that after differentiating 102 times, the first 3 terms of f(x), as well as the constant term, will vanish.
Recall the chain rule:
![\bigg(f(g(x))\bigg)' = f'(g(x)) * g'(x)](https://img.qammunity.org/2023/formulas/mathematics/college/kx7nh0ttutddjg87x33a4hip06j44tyrne.png)
Then the first few derivatives of the exponential term are
![\left(e^(2x)\right)' = e^(2x) * (2x)' = 2e^(2x)](https://img.qammunity.org/2023/formulas/mathematics/college/965cqonf0kburubvjuepzzev2bdkrgo1np.png)
![\left(e^(2x)\right)'' = 2\left(e^(2x)\right)' = 2^2e^(2x)](https://img.qammunity.org/2023/formulas/mathematics/college/47uhnxxnn4bpldilip9hvunbg17kkx0ykv.png)
![\left(e^(2x)\right)^((3)) = 2^2\left(e^(2x)\right)' = 2^3e^(2x)](https://img.qammunity.org/2023/formulas/mathematics/college/inj2wpmtnyiolsqfr2viejbctjesvdhovz.png)
and so on, with n-th derivative
![\left(e^(2x)\right)^((n)) = 2^ne^(2x)](https://img.qammunity.org/2023/formulas/mathematics/college/id7zl8prxbbh8xs297ql9aht0i95oypxhf.png)
Putting everything together, we have
![\boxed{f^((102))(x) = -2^(102)e^(2x)}](https://img.qammunity.org/2023/formulas/mathematics/college/75a5ndp06iwe8fa2kitb8udi25q0icsnuv.png)